Sistem Penjualan Produk Berbahan Tais Berbasis Online Di Toko Market Dili - Tjatursari Widiartin; Aricia Maria Inacio Correia (Informatics Department-Universitas Wijaya Kusuma Surabaya, 2022)
Timor Leste is a country that is rich in tourism potential such as natural beauty, historical tourism and cultural heritage. One of the tourist attractions that are still being developed in the lives of the people of Timor Leste is cultural heritage. Woven cloth or tais is one of the local cultural heritages which is still used in the life of the people of Timor Leste. The method used in the development of this software is the waterfall method. The waterfall method has several structured stages, namely: requirements analysis, system and software design, implementation, integration and testing, maintenance. The aim of this research is to produce an Online-Based Tais Product Sales System in the Dili Market as an effort to increase marketing and sales promotions. This sales system makes it easier for the public to access information about woven fabric products at the Dili Market online.